Exergoeconomic performance optimization for a regenerative closed-cycle gas turbine combined heat and power plant. (November 2019) - Feng, Huijun; Tao, Guisheng; Tang, Chenqi; Ge, Yanlin; Chen, Lingen; Xia, Shaojun
Abstract: A combined heat and power plant with regenerative closed-cycle gas turbine is considered. The heat transfer losses, irreversible adiabatic losses and irreversible pressure drop losses are considered in the plant. The expressions of dimensionless profit rate and exergy efficiency are gained. The optimal heat conductance distributions and compressor pressure ratio are derived based on maximum dimensionless profit rate and maximum exergy efficiency objectives, respectively. The results show that the heat conductance distributions and compressor pressure ratio have their optimal values which results in maximum dimensionless profit rate. The curve of maximum dimensionless profit rate and the corresponding exergy efficiency is loop-shaped one. With the increases in heat reservoir temperature ratio τ 1, price ratios a and b as well as total heat exchanger inventory U T, the maximum dimensionless profit rate increases. With the decrease in a and increases in τ 1, b and U T, the corresponding exergy efficiency increases. The heat reservoir temperature ratio τ 2 has its optimal value which leads to double maximum dimensionless profit rate. Moreover, the maximum exergy efficiency performance of the plant is also analyzed. Because the exergoeconomic performance of irreversible regenerative closed-cycle gas turbine cogeneration plant has not been investigated by the researchers before, the exergoeconomic performance optimization is conducted in this paper, and the results obtained can offer new design guidelines for this kind of cogeneration plants. Highlights: A CHP plant with real regenerative closed-cycle gas turbine is considered. Heat transfer, irreversible compression and expansion and drop losses are considered. Dimensionless profit rate and exergy efficiency are derived. Heat conductance distributions and compressor pressure ratio are optimized.